TINJAUAN HUKUM PERSAINGAN DAN PENGHAPUSAN MEREK DAGANG TERDAFTAR - SULTHAN FAISAL ESA M; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2022)
Indonesia's trademark regulations are constantly changing and are governed by Law No. 21 of1961 on the use of trademarks and first-to-file principles, which assumes that the party with theright to use the trademark is the first registrant of the trademark. increase. However, with theongoing amendments to the law, Law No. 21 of 1961 was amended to Law No. 19 of 1992, withchanges related to the license system that was originally the first system or declaration used. Wasdone. First registration system & # 40; Stelsel to the first used system & # 41 ;. File system orconstructive stells). This search uses a library search type that looks up various documents relatedto the search. The method used by the author is a normative legal investigation method using alegal approach and a case approach. The result is that Law No. 20 of 2016 states that thetrademark of Geprek Bens, owned by Ruben Samuel Onsu, must be revoked and rejected by thestate's Genderral Haku Kekayan Intellectual. It shows that it is.